LANGUAGE ATTITUDE IN UZBEKISTAN (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2025)
This survey was conducted to collect ideas and accurate information about the main aspects of the language in Uzbek society; the field of education and career, additonally its role in social relations. Answers to the questions were received from the students of Kimyo International University in Tashkent. It was mainly conducted to examine students' opinions about the importance of languages in students' daily lives, their attitudes towards dialects, and the impact of language use in various social settings.